Experience of Safety and Health Promotion in Dolomites Area - Marcotriggiano, Vincenzo; Prete, Alice; Padoin, Angela; Canal, Chiara; Bino, Erica; Lovat, Alberto; Campigotto, Igor; Campigotto, Flavia; Maggiolo, Adriana; Vedana, Gianna; Fagherazzi, Jacopo; Manzi, Mattia; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
The mountain context represents a suitable setting for promoting health. In view of the Olympic Games, which are expected to take place in the Dolomites area in 2026, the outdoor Alpine environment must continue to meet all the health and safety requirements. Our recent experience, implemented in this area since summer 2024 through the Prevention Department of the Local Health Authority ULSS 1 Dolomiti, aims to encourage multi-sector preventive public health policies, in order to improve the “Shelters” (“rifugi”, in Italian) hygiene, to strengthen the safety requirements, and to implement preventive projects.